Studi Komparatif Stabilitas Timbunan Tanah dengan Perkuatan Sabut Kelapa Menggunakan Software GeoStudio Slope/W terhadap Hasil PLAXIS - Trianto, Adden; Pradhana, Rakhan Dhawy; Fansuri, Muhammad Hamzah (Universitas Ibn Khaldun, 2025)
Infrastructure development often faces slope stability challenges due to suboptimal soil conditions. One possible solution is the use of coconut coir as a soil reinforcement material to improve slope stability. This study analyzes the stability of embankment slopes reinforced with coconut coir using GeoStudio Slope/W 2012 software with the limit equilibrium Method and compares the results with Fahriani's (2016) study, which utilized Plaxis. The analysis was conducted on embankment slopes with varying percentages of coconut coir addition (0%–5%) using five limit equilibrium Methods: Morgenstern-Price, Spencer, Bishop Simplified, Janbu Simplified, and the Ordinary Method of Slices. The results indicate that all analysis Methods show an increase in the factor of safety (FoS) as the percentage of coconut coir increases. The comparison with Plaxis results shows a small FoS difference, ranging from 0.154% at 0% coconut coir to 1.397% at 5% coconut coir, with 0%–3% having a difference of less than 1%, indicating that both Methods provide relatively consistent results. The trend of increasing the factor of safety due to the addition of coconut coir remains similar in both software programs, reinforcing the effectiveness of coconut coir as a slope reinforcement material.